Survival rate and development of larvae Elaeidobius kamerunicus (Coleoptera: Curculionidae) on artificial diets - Sarah Najihah Mohd Zahari,; Rosha Rusli,; Mohamad Haris Hussain,; Johari Jalinas, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The weevil Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) was introduced within the oil palm industry in Malaysia to improve the yield of the oil palm production. However, there were reduction of pollination towards the oil palm plantation by the E. kamerunicus. Therefore, the purpose of this study was to develop an artificial diet for E. kamerunicus to maintain larvae and compare the development under laboratory conditions in different artificial diets. Four types of artificial diets have been prepared where diet a and diet b used ingredients such as yeast, wheat, corn flour, ascorbic acid, benzoic acid, for bacteriology, distilled water, methyl-4-hydroxibenzoate and chloramphenicol. Diet c and diet d were formulated by yeast, wheat flour, corn flour, honey, milk powder and glycerol. An additional diet which contained oil palm male flowers were introduced in diet b and d. The pupation and survival rate of E. kamerunicus between the four diets under laboratory conditions were recorded. The results showed that diet d produced the highest pupation and emerged adults compared to other diets with 56% of both pupation and emerged adults out of total 25 larvae. The survival rate curved (y=mx+c) of larvae E. kamerunicus showed the least slope with m value equal to -1.2242 which showed highest survival rate of the larvae.